PELUANG, TANTANGAN, DAN MASA DEPAN UKM COFFEE SHOPP KOPI. US - Ergo Nurpatria Kurniawan; Ali Hamdan Syafari; Mauzia Awalia; Hotria Siregar (LPPM STEBIS YPII, 2026)
COFFE SHOP KOPI.US is a micro-scale coffee business founded by a married couple, Fahru Rozy and Tiya, in Dayeuh Village, Cileungsi, Bogor Regency, West Java. The business began in early May 2025 and focuses on selling robusta-based milk coffee using natural palm sugar. The initiative emerged from the owners’ passion for coffee and the desire to develop a sustainable home-based business after the COVID-19 pandemic. This paper describes the development of KOPI.US, including its production methods, marketing strategy, financial structure, and challenges. The study aims to illustrate how small-scale businesses can thrive through creativity, skill improvement, and social media-based marketing. The findings show that even with minimal capital, entrepreneurial spirit and innovation can create a profitable and sustainable local enterprise.